Role of NHM trainings to rural masses in value addition of underutilized fruits and vegetables (Indian Journal of Arid Horticulture, 2013)
Horticultural produces grown in Rajasthan are of  explicit quality with great nutritional, meditational and  economic importance. Some of the fruit like aonla, jamun,  tamarind, phalsa, custard apple, karonda, kainth and bael  etc. and vegetables such as kachri, beans, bakla, kakora,  guar and moringa etc. are successfully grown with  minimum care on waste land and provide food and  nutritional security to the rural masses.
Keywords: abundantly; Rural masses